Septic femoral shaft non-union treated by one-step surgery using a custom-made intramedullary antibiotic cement-coated carbon nail: case report and focus on surgical technique - Bonicoli, Enrico; Piolanti, Nicola; Giuntoli, Michele; Polloni, Simone; Scaglione, Michelangelo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: In the orthopaedic and traumatological fields septic non-unionsrepresent a severe complication, hard to manage and treat. Traditionally, the surgical technique consists in totwo sequential steps: debridement with administration of local and systemic antibiotics associated with temporary stabilization of the fracture and subsequent reconstruction of bone and soft tissues. Recently, the use ofsome devices to treat septic non-union by one-step surgery have been introduced with encouraging resultsMethods: We reported our experience with a case treated by one-step procedure using a custom-made intramedullary antibiotic cement-coated carbon nail. We reviewed the literature and described the surgical technique employed in this case. Results: At 6 months from surgery the patient was able to perform full weight-bearing and carry out the normal activities of daily living. Serum inflammatory markers normalized and radiographic controls showed the presence of a mechanically good bone callus at the non-union site. The bone resection carried out determined a limb length discrepancy of 3 cm, that was corrected through a temporary shoe lift, currently well tolerated. The patient regained full ROM of the right knee. Conclusion: Intramedullary antibiotic cement-coated nail associated with systemic antibiotic therapy proved to be an effective treatment to control the infection and provide immediate stability at the septic non-union/fracture site, allowing a rapid functional recovery. It represents a valid option especially in patients who refuse external devices or surgical additional procedures, as in our case. (www.actabiomedica.it)